The "Temporary Concentration" Model: A Breakthrough in Curriculum Design for Integrating Dual-Competencies in Indonesian Islamic Universities' Arabic Language and Literature Program - Erfan Gazali; Wulandari Wulandari (Indonesian Journal of Arabic Studies, 2024)
Purpose: This study investigates the "Temporary Concentration" model, an innovative curriculum design implemented in the Arabic Language and Literature (BSA) program at UIN Siber Syekh Nurjati Cirebon, Indonesia. It aims to deconstruct how this model facilitates the integration of dual linguistic and literary competencies within the rigid structural constraints of the national higher education system, specifically the credit limit (144-160 SKS) mandated by national policy. Methods: Employing a qualitative, instrumental single-case study design underpinned by a constructivist paradigm, this research collected data through in-depth analysis of curriculum documents, semi-structured interviews, and focus group discussions with key stakeholders, including curriculum designers, lecturers, and students. The data were analyzed using thematic analysis (Braun & Clarke, 2006) to identify emergent themes regarding the model's design, implementation, and perceived efficacy. Findings: The analysis reveals that the model strategically allocates 44 SKS (29.5% of the total 149 SKS curriculum) to an intensive, two-semester concentration in either Linguistics or Literature. This structured immersion phase ensures deep disciplinary mastery, successfully allocating 33% and 37.2% of the total curriculum to linguistics and literature, respectively—a significant increase compared to conventional BSA programs. The model effectively resolves the epistemological tension between depth and breadth by providing a clear roadmap for specialization before integration, addressing a key concern in curriculum literature. Research Implications: The study offers a viable prototype for curriculum reform in similar contexts, demonstrating that strategic reconfiguration, rather than credit expansion, can overcome policy-practice misalignments. It provides practical guidance for program managers and contributes to theoretical discourse by introducing a novel "temporary concentration" framework for dual-competency integration in constrained educational environments.